Malaysia Economic Monitor, November 2009 : Repositioning for Growth - World Bank (World Bank, 2012)
Malaysia is emerging from one of the worst export slumps in its economic history as manufacturing and exports have started growing again. With East Asia leading the recovery and advanced economies showing progressive improvement, the Malaysian economy is projected to grow at 4.1 percent in 2010, following a contraction of 2.3 percent in 2009. The medium-term outlook remains promising with growth reaching 5.6 and 5.9 percent in 2011 and 2012, respectively, though that will depend on sustained global recovery from the crisis. The overriding medium-term challenge is for the Malaysian economy to join the select group of high-income countries. Malaysia has experienced solid growth over the last decades, but has relied on an economic model predominantly based on capital accumulation, although private investment rates never recovered from their 20 percentage point fall after the Asian 1997/98 crisis and are now among the lowest in the region. For Malaysia to climb the next step up the income ladder, it needs to focus on improving the investment climate to raise investment rates and focus on productivity growth. Against this backdrop, the authorities are developing a 'new economic model,' which will be squarely centered on boosting productivity. Promising reforms have already been announced in the areas of services and foreign direct investment, which will help revitalize private investment.